Characteristics associated with the development of hard and soft skills in accounting - Severino, Carolina; Silva, Denise Mendes da (Advances in Scientific and Applied Accounting, 2024)
Objective: Evaluate the association between curricular aspects, active methodologies, determinants of academic performance and the development of skills and abilities in the perception of students and professors of the undergraduate course in Accounting Sciences. Method: The research was conducted by applying questionnaires to a sample of 170 students and 23 teachers from the undergraduate course in Accounting Sciences at a federal university in Minas Gerais. For data treatment and analysis, descriptive statistics, mean tests, and non-parametric tests were used. Results: The results indicated that the analyzed variables are associated with the development of skills and technical competences. In addition, an alignment was identified between the perception of students and professors surveyed regarding the importance of technical skills, abilities, and attitudes. Contributions: This study advances in relation to previous research insofar as it proposes a joint approach to the variables: skills, abilities, curriculum, active methodologies, and academic performance, in addition to contemplating students and professors, to identify how the associations between these variables are perceived in the academic environment, contributing to the related literature. In addition, the study contributes to accounting education, at an institutional level (course management) and social level (students and professors’ performance) in two perspectives: i) it enables the understanding of the synergy of these variables in the training of accountants, so that they are able to deal with a dynamic and globalized business environment; and ii) demonstrates how competence-based training, advocated internationally, notably with regard to the development of professional skills, can be achieved through the pillars of the teaching-learning process (students, teachers, curriculum, method and performance).